Involvement of AT1 angiotensin receptors in the vasomodulatory effect of des-aspartate-angiotensin I in the rat renal vasculature - Dharmani, M.; Mustafa, Mohd Rais; Achike, F.I.; Sim, M.K. (Elsevier, 2008)
Angiotensin II is known to act primarily on the angiotensin AT1 receptors to mediate its physiological and pathological actions. Des-aspartate-angiotensin I (DAA-I) is a bioactive angiotensin peptide and have been shown to have contrasting vascular actions to angiotensin II. Previous work in this laboratory has demonstrated an overwhelming vasodepressor modulation on angiotensin II-induced vasoconstriction by DAA-I. The present study investigated the involvement of the AT1 receptor in the actions of DAA-I on angiotensin IIinduced vascular actions in the renal vasculature of normotensive Wistar–Kyoto rats (WKY), spontaneously hypertensive rats (SHR) and streptozotocin (STZ)-induced diabetic rats. The ﬁndings revealed that the angiotensin receptor in rat kidney homogenate was mainly of the AT1 subtype. The AT1 receptor density was signiﬁcantly higher in the kidney of the SHR. The increase in AT1 receptor density was also conﬁrmed by RT-PCR and Western blot analysis. In contrast, AT1 receptor density was signiﬁcantly reduced in the kidney of the streptozotocininduced diabetic rat. Perfusion with 10 9 M DAA-I reduced the AT1 receptor density in the kidneys of WKY and SHR rats suggesting that the previously observed vasodepressor modulation of the nonapeptide could be due to down regulation or internalization of AT1 receptors. RT-PCR and Western blot analysis showed no signiﬁcant changes in the content of AT1 receptor mRNA and protein. This supports the suggestion that DAA-I causes internalization of AT1 receptors. In the streptozotocin-induced diabetic rat, no signiﬁcant changes in renal AT1 receptor density and expression were seen when its kidneys were similarly perfused with DAA-I.